Gross Morphometric Study on Pineal and Pituitary Glands of Jaffarabadi Buffalo During Different Seasons of the Year - Sharma, Anil (Indian Journal of Veterinary Anatomy, 2020)
The present study was conducted on pineal and pituitary glands of 30 Jaffarabadi buffaloes to evaluate the changes in gross morphology and biometry during winter, summer and monsoon seasons. The pineal gland of Jaffarabadi buffaloes was a small pea shaped organ, located in the median plane just in front of two rostral colliculi. The pituitary gland was elongated and roughly boat shaped or pyriform shaped and situated in sella turcica of the sphenoid bone. No significant differences were observed in the location, shape and color of pinealand pituitary glands during different seasons. The weight, volume and thickness of pineal gland were significantly higher during the summer as compared to the winter and monsoon seasons whereas length and width did not show any significant changes during different seasons. The occurrence and size of grossly visible brain sand was higher in the pineal glands during the summer season. The weight and thickness of pituitary gland was significantly higher during monsoon and summer as compared to the winter season whereas no changes were observed in volume, length and width during different seasons.